Existence and quiddity in the later Ash'arite kalam a study on al-Iji's al-Mawaqif and al-Jurjani's Sharh al-Mawaqif - Mohd Zaidi Ismail (Islamic and Strategic Studies Institute, 2017)
Aimed at shedding some light on the intellectual process that historically led to the sophisticated elaborations and analyses of existence (wujūd) and quiddity (māhiyyah) by such later Ṣūfī metaphysicians as 'Abd al-Raḥmān al-Jāmī, 'Abd al-Ghanī al-Nāblusī, Mullā Ṣadrā and others, the present work explores the position of a school of thought in the Islamic history-that is to say, later ash'arisms as represented primarily by its two famous mutakallims, one from the 7th/8th century of Hijrah and the other from the 8th/9th century, namely: 'Aḍud al-Dīn 'Abd al-Raḥmān al-Ījī (d. 756 H.) and al-Sayyid al-Sharīf 'Alī b. Muḥammad al-Jurjānī (d. 816 H.)-which was directly and actively involved in the intellectual debates about the nature of existence and quiddity that resulted in a creative synthesis of the aforementioned metaphysicians. It is therefore an attempt to survey how these two mutakallims, the former being the main actor and the latter being his commentator, dealt with the various positions adopted pertaining to the nature of existence and its relation to quiddity. In so doing, it selects al-Ījī's widely acclaimed kalām manual, al-Mawāqif, and the most famous among its many commentaries, the one done by al-Jurjānī.